INTERLINGUAL HOMONYMS IN SPANISH AND ITALIAN: FALSE FRIENDS – REAL ENEMIES OF TRANSLATORS - Taras E. Pysmennyi; Aleksander A. Pliushchai; Marianna Yu. Onishchenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2019)
In modern philological science, similar in sound but different in meaning words are called interlingual homonyms or, as they are often called in the circles of philologists and translators, “false friends”. Such “false friends” are “real enemies” for translators. However, there is no difference whether translation is carried out between related language groups or into other foreign languages. In this work, we will study and disclose the problems of translation and interpretation of interlingual homonyms in Spanish and Italian, being part of the group of Romance languages. The problem posed is one of the most complicated touching important aspects of the activities of modern translators. And the goal of this work is to analyze the problem of translating interlingual homonyms with the subsequent proposal to simplify understanding and study the phenomenon of homonymy. It is assumed that the list of Spanish-Italian homonyms presented in the research can be of substantial help in the practice of teaching these languages for both foreign students from European countries and students who are fluent in Italian or Spanish. In the future, our methodological developments can form the basis of a special textbook on Spanish-Italian vocabulary, oriented primarily for European students and taking into account the problem of interlingual interference. In addition to the list of interlingual homonyms, the authors created a bilateral dialogue between native speakers of Spanish and Italian, where a simple, at first glance, conversation from life that leads to unpredictable unfolding and to no less unexpected ending, perfectly demonstrates what ignorance can lead to misunderstandings without clear interpretation of certain words. The authors propose to use a visual demonstration of interlingual homonyms in such situational dialogues, which will help students and translators to clearly understand the differences between certain words, and, accordingly, facilitate the perception of the material under consideration.